Standardization of Non-specific Parameters of Honey from Farmed Bees in Tojo Una Una - Islamiati, Utami; Parobe, Alda Iglesias; Yanuarty, Rezky; Tandi, Joni (Jurnal Biologi Tropis, 2024)
Honey is a normally sweet arrangement delivered by bumble bees from nectar sources. In the use of honey as an herbal ingredient, however, not all honey in Indonesia has been standardised, so it is necessary to confirm the quality of honey that meets the reference standards set by the government, namely SNI. The purpose of this study was to determine the quality of honey in Tojo Una-una Regency from three different sub- districts: Ampana Tete, Ampana Kota, and Ratolindo, based on standardization using non-specific test parameters. This study used pure honey and honey extract using 96% ethanol solvent. The tests based on non-specific parameters in the form of moisture content were performed by gravimetry, ash content by dry ashing, acidity by titration, and reducing sugar by UV-Vis spectrophotometry, while metal contamination by atomic absorption spectrophotometry, all tests were repeated 3 times. Statistical test results showed that there were significant differences in the quality of honey from three different locations. The results of the research on pure honey and honey extract from Ampana Tete meet the SNI requirements except for the water content test of pure honey which does not meet the SNI.